Late Quaternary activity of Wulashan Northern fault, North China - Wei, Leihua; He, Weimin; Xu, Yueren; Du, Yanlin; Dai, Aopeng; Song, Xiaopeng; Xu, Shuya; Qin, Jingjing (Frontiers in Earth Science, 2024)
The Late Quaternary activity characteristics of secondary faults located between the main active faults at the boundaries of large basins are of great significance to the overall understanding of regional seismic hazards. The Wulashan Northern Fault (WNF) is located on the northern side of the Ordos Block, within the Northern Margin Fault Basin in North China, between the Sertengshan Piedmont Fault and Daqingshan Piedmont Fault. Current research on the geometry and kinematics of the WNF needs to be improved. In this study, we aimed to determine the shallow structural characteristics and Late Quaternary activity of the WNF using shallow seismic exploration and composite drilling geological cross-sectional analysis. The results indicate that the WNF is not a single surface fault but multiple branches with a northward-dipping stepped surface distribution. The latest activity of the F1 branch with a maximum coseismic vertical dislocation of 0.9 m occurred before 47.08 ±3.7 ka B.P. The latest and older activities of the branch of F2 with a maximum coseismic vertical dislocation of 0.96 m and 1.15 m occurred before 73.8 ±2.8 ka B.P. and 91.2 ±4.4 ka B.P., respectively. According to a series of empirical relationships between length of surface rupture and magnitude, the maximum potential magnitude of the earthquake was determined to be M=6.5~7.0. We argue that even though the Late Quaternary activity of the WNF was weaker than that of the other boundary faults of the Hetao Basin, the local urban and rural planning and land and resources construction in the Hetao Basin region should pay attention to the seismic risk of the WNF as an independent section in the future for the effect of secular tectonic loading.M=8.0 or even more significant in history (Figure 1). The strong earthquakes have caused devastating disasters to people and the economy around each epicenter, such as the 1739 A.D. M=8.0 Pingluo earthquake in the Yinchuan Basin (The Research Group on Active Fault System around